"They Take Away What We Are": Contributions of a Participatory Process with Photovoice to the Capabilities for Epistemic Liberation of Young People. Issue 1 (2nd January 2022) - Leivas Vargas, Monique; Maicas-Pérez, Marta; Monge Hernández, Carmen; Fernández-Baldor, Álvaro
ABSTRACT: Young people have historically been marginalised and excluded from decision-making related to city life and territorial planning. Relegated to exercising a passive role until the reach of the legal age, young people suffer oppressions that can occur from a banking education perspective at secondary education. Using the Freirian approach to liberating education, we identify four oppressions that can occur at a structural level and in the communicative interactions between students and teachers: ontological, epistemic – expressive and interpretive – and epistemological oppressions. In this article, we analyse a photovoice experience "They take away what we are" developed with 27 young high school students' at the city of Valencia, Spain. This participatory process has strengthened the four capabilities for the epistemic liberation of the students: the capability to be and recognise oneself as a producer of valid knowledge; the capability to do from teamwork, in the neighbourhood and with the people who inhabit it; the capability to learn from different local and global knowledge; and the capability to transform space through collective action. This photovoice experience has raised the voices of youth about what they want to be, the life they want to live and the territories they dream of inhabiting.